2013
DOI: 10.1210/jc.2012-2978
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto's Thyroiditis and Papillary Thyroid Carcinoma: Is There a Correlation?

Abstract: Although limited by the lack of definitive pathology, population-based FNA studies did not find a statistically significant correlation between HT and PTC. Thyroidectomy studies, which reported a statistically significant positive correlation, are subject to selection bias. More prospective studies with longer follow-up are needed to further elucidate this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
182
3
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(205 citation statements)
references
References 37 publications
7
182
3
13
Order By: Relevance
“…As recently underlined by Fiore et al in their review [16], different degrees of association were found if cytological or histological series were considered [18][19][20]. As hypothesized by the Authors themselves [19], this result could be strongly influenced by a selection bias: if cytological examination is usually performed in patients with ultrasound suspicious thyroid nodules (i.e.…”
Section: Thyroid Cancer and Autoimmunity: Epidemiological And Clinicamentioning
confidence: 97%
See 1 more Smart Citation
“…As recently underlined by Fiore et al in their review [16], different degrees of association were found if cytological or histological series were considered [18][19][20]. As hypothesized by the Authors themselves [19], this result could be strongly influenced by a selection bias: if cytological examination is usually performed in patients with ultrasound suspicious thyroid nodules (i.e.…”
Section: Thyroid Cancer and Autoimmunity: Epidemiological And Clinicamentioning
confidence: 97%
“…As hypothesized by the Authors themselves [19], this result could be strongly influenced by a selection bias: if cytological examination is usually performed in patients with ultrasound suspicious thyroid nodules (i.e. with high a priori probability of malignancy), thyroidectomy, instead, is frequently performed in patients with GD (to treat hyperthyroidism) or due to compressive symptoms in subjects with large nodular goiter and coexisting AITD.…”
Section: Thyroid Cancer and Autoimmunity: Epidemiological And Clinicamentioning
confidence: 99%
“…Hashimoto's thyroiditis (HT) is the most common autoimmune thyroid disorder. Hallmark of HT is the progressive loss of thyroid epithelial cells that are replaced by an infiltration of mononuclear cells (T cells) that eventually leads to thyroid atrophy and hypothyroidism (Caturegli et al 2013, Jankovic et al 2013.…”
Section: Thyroiditis and Thyroid Cancermentioning
confidence: 99%
“…On the basis of FNA studies including over 18 000 patients, the prevalence of PTC in HT is estimated to about 1.2% with a non-significant risk ratio (RR) of 0.69. In contrast, prevalence of PTC in HT based on about 10 000 archival thyroid specimens is 27% (RR 1.59; Ott et al 1987, Kashima et al 1998, Loh et al 1999, Kebebew et al 2001, Jankovic et al 2013. Thus, limiting the analysis to archival thyroidectomy specimens might carry a selection bias because the indication for surgery is commonly due to the presence of suspicious nodules.…”
Section: Thyroiditis and Thyroid Cancermentioning
confidence: 99%
“…For the first time it's been described by Hakaru Hashimoto a Japanese surgeon who worked in Berlin, Germany (2,3).The annual incidence of HT is estimated to be around 0,3-1,5case for 1000 individuals and it more prevalent in females than in males with a ratio going from 5 until 20:1 (4,5).The same is for papillary thyroid cancer (PTC). Itis the most prevalent form of thyroid cancer around 70-80% of all thyroid cancer.It's more prevalent in females than males (6).Correlation between HT and PTC is first described from Dailey et al in 1955 (7).From that time and now it's still an open debate and the dates are still controversial. Some study report a positive correlation between 11 until 36 % (8 -11) and other didn't observed any correlation (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%